Reduced mortality during the COVID-19 outbreak in Japan, 2020: a two-stage interrupted time-series design. (28th October 2021) - Onozuka, Daisuke; Tanoue, Yuta; Nomura, Shuhei; Kawashima, Takayuki; Yoneoka, Daisuke; Eguchi, Akifumi; Ng, Chris Fook Sheng; Matsuura, Kentaro; Shi, Shoi; Makiyama, Koji; Uryu, Shinya; Kawamura, Yumi; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) continues to be a major global health burden. This study aims to estimate the all-cause excess mortality occurring in the COVID-19 outbreak in Japan, 2020, by sex and age group. Methods: Daily time series of mortality for the period January 2015–December 2020 in all 47 prefectures of Japan were obtained from the Ministry of Health, Labour and Welfare, Japan. A two-stage interrupted time-series design was used to calculate excess mortality. In the first stage, we estimated excess mortality by prefecture using quasi-Poisson regression models in combination with distributed lag non-linear models, adjusting for seasonal and long-term variations, weather conditions and influenza activity. In the second stage, we used a random-effects multivariate meta-analysis to synthesize prefecture-specific estimates at the nationwide level. Results: In 2020, we estimated an all-cause excess mortality of −20 982 deaths [95% empirical confidence intervals (eCI): −38 367 to −5472] in Japan, which corresponded to a percentage excess of −1.7% (95% eCI: −3.1 to −0.5) relative to the expected value. Reduced deaths were observed for both sexes and in all age groups except those aged <60 and 70–79 years. Conclusions: All-cause mortality during the COVID-19 outbreak in Japan in 2020 was decreased compared with a historical baseline. Further evaluation of cause-specific excess mortality is warranted.